Subjective Well-Being pada Wanita Dewasa Awal yang Belum Menikah - Marlenda T. Selan; Engelina Nabuasa; Yeni Damayanti (Universitas Nusa Cendana, 2020)
Generally married is done in early adult period which is at the age of 18 until 40 but the fact found that are still several people who are still single at those ages. Early adult women who are still single or not married can cause the negative perspective from society where they are living with the result they cannot adapt very well in their environment because of the pressure and insult from those people who make them feel shy and do not want to have social connection. This condition can be decreased when they have high subjective well- being where she is able to do things that make her happy to gather with family, recreation and others. Subjective well-being is an individual evaluation toward themselves through affective evaluation. Those are negative and positive affect and cognitive evaluation or self-satisfaction. The purpose of this research is to find out the subjective well-being picture of early adult women who have not married yet in Liliba disrict. This is qualitative research with descriptive method. This research uses three participants of early adult women whose found by purposive sampling technique characterized by single women at the age of 30 until 40 years old in Liliba district. The result found that three participants have different subjective well-being pictures where HL has positive affect and feels satisfy with her life now. Whereas LA and RF have more negative affect and still feel unsatisfied with their lives.